The Effect of the Advance Organizer Learning Model on the Social Literacy Ability of Grade IV Students of SDS IT Delisha Tandam Hilir - Purwanti, Siska; Fatmawati, Fatmawati; Widodo, Hadi; Yusrizal, Yusrizal (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
This study aims to determine the effect of the Advance Organizer learning model on students’ social literacy skills compared to conventional learning models. The research employed a true experimental design with non-probability sampling, involving 27 fourth-grade students as the experimental class and 27 fifth-grade students as the control class. The research instrument was a social literacy test administered through pretest and posttest. Data analysis included normality test, homogeneity test, and t-test using SPSS version 26. The results showed that the data were normally distributed (Sig. 0.188 > 0.05) and The t-test obtained a significance value of 0.013 < 0.05, indicating a significant difference between the learning outcomes of students in the experimental class and the control class. The average posttest score of the experimental class was 86.30, while the control class scored 79.26. Thus, it can be concluded that the application of the Advance Organizer learning model is more effective in improving students’ social literacy skills compared to conventional learning models